2021
DOI: 10.22219/procedia.v8i4.14787
|View full text |Cite
|
Sign up to set email alerts
|

Terapi keluarga untuk memperbaiki pola komunikasi orang tua dan anak

Abstract: Komunikasi antara orang tua dan anak merupakan hal yang pentingdalam keluarga. Masalah yang terjadi pada kasus ini yaitu komunikasiyang tidak efektif antara anak dan orang tua yang dikarenakantidak terjalinnya komunikasi secara langsung sehingga membentukpola perilaku yang berulang. Seluruh anggota keluarga hanyamemendam pemikirannya masing-masing. Anggota keluarga tidak adayang menyampaikan pendapatnya secara terbuka dan mencoba untukmenyelesaikan masalah yang terjadi di dalam keluarga. Pola asuhyang diterapk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
5

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
(7 reference statements)
0
3
0
5
Order By: Relevance
“…Several studies related to therapy given to slow learners as a curative measure, namely: as found by [9] that art therapy was an alternative assistance in supporting the academic, emotional and moral-social development of children with special needs. [10] found that that family therapy had an important role in meeting the needs of slow learners. [11] found that through Child Centered Play Therapy (CCPT) was a therapeutic method that could be used to increase self-esteem in children with slow learners.…”
Section: State Of the Artmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies related to therapy given to slow learners as a curative measure, namely: as found by [9] that art therapy was an alternative assistance in supporting the academic, emotional and moral-social development of children with special needs. [10] found that that family therapy had an important role in meeting the needs of slow learners. [11] found that through Child Centered Play Therapy (CCPT) was a therapeutic method that could be used to increase self-esteem in children with slow learners.…”
Section: State Of the Artmentioning
confidence: 99%
“…Slow learners need longer time to understand certain things, both about learning and in understanding certain instructions that really suitable for student [17]. As found by [10] that slow learners have abilities below the average but cannot be called a disability. Physically and socially slow learners do not show any difference with children in general.…”
Section: Lesson For Slow Learners At Muhammadiyah Alam Surya Mentari ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Psikoislamika: Jurnal Psikologi dan Psikologi Islam 661 26 Terapi keluarga untuk memperbaiki pola komunikasi orang tua dan anak (Ariani, 2020).…”
Section: The Dynamics Of Parents and Children Communication: A Scopin...unclassified
“…Problem yang menghambat keakraban dalam keluarga pada awalnya ditandai komunikasi interpersonal antar anggota keluarga yang tidak lancar. Beberapa anggota memilih untuk diam daripada menyelesaikan masalah (Ariani, 2020;Awi et al, 2016. ) Hasil-hasil penelitian tersebut menginformasikan upaya-upaya ilmiah untuk mengatasi masalah komunikasi dalam keluarga dan mencapai keharmonisan keluarga.…”
unclassified